Associations of eccentric force variables during jumping and eccentric lower-limb strength with vertical jump performance: A systematic review - Nishiumi, D.; Nishioka, T.; Saito, H.; Kurokawa, T.; Hirose, N. (PLOS ONE, 2023)
The purpose of this systematic review was to summarize the associations of eccentric force variables during jumping and eccentric lower-limb strength with vertical jump performance. A literature search was conducted in September 2022 using PubMed, Web of Science, and Scopus. Thirteen cross-sectional studies investigating the relationship between eccentric force and strength variables, such as force, rate of force development (RFD), power, time, and velocity, and vertical jump performance, including the jump height, reactive strength index (RSI), and reactive strength index-modified (RSImod), were included in this systematic review. As eccentric strength, variables during the unloading-to-braking phase of countermovement jump (CMJ) (force, RFD, etc.) and the eccentric force of the squat movement and knee joint were included. The CMJ height, RSImod, and drop jump RSI were included to analyze the vertical jump performance. The modified form of the Downs and Black checklist was used to evaluate quality. Associations between the force and RFD during the descending phase of the CMJ and jump height were observed in some studies but not in others, with differences between the studies. Some studies reported associations between the force and/or RFD during the descending phase of the CMJ and RSImod of the CMJ, with no differences among their results. In addition, there are associations of the eccentric forces during squatting and knee extension with the CMJ and the drop jump heights and RSI of the drop jump. The eccentric force variables in the CMJ and RSImod are related; however, their relationship with jump height remains unclear. Furthermore, improved eccentric muscle strength may contribute to vertical jump height because of the associations of the eccentric strength during knee extension and squatting with jump height.